Pregabalin use in forensic hospitals and prisons in German speaking countries—a survey study of physicians - Novotny, Michal; Bulla, Jan; Hubl, Daniela; Fischer, Sebastian Karl Maximilian; Grosshans, Martin; Gutzeit, Andreas; Bilke-Hentsch, Oliver; Seifritz, Erich; Mutschler, Jochen (Frontiers in Public Health, 2024)
Background Pregabalin is a gamma-aminobutyric acid (GABA) analog that was approved in the EU in 2004 for the treatment of neuropathic pain, generalized anxiety disorder and epilepsy. Since its introduction, pregabalin abuse and misuse has increased significantly. In Switzerland, clinical reports suggest that pregabalin misuse is common among patients in forensic hospitals and prisons. However, data on pregabalin use is scarce, especially in these settings. Therefore, we conducted a study to explore patterns of pregabalin use among prison and forensic patients. Methods We used a questionnaire to survey physicians working in prison and forensic medicine in German-speaking countries. A total of 131 responses were received. Results According to the physicians' subjective assessment, 82.5% of them had observed a recent increase in pregabalin use by their patients and 89.1% of them reported that their patients requested pregabalin without a clear medical indication. Patients misusing pregabalin in combination with other illicit substances were observed by 93.3% of the physicians surveyed. According to 73.5% of the physicians surveyed, they had already encountered patients on pregabalin doses of more than 600 mg/day (the maximum recommended daily dose); the highest dose reported was 4,200 mg/day. According to 85.0% of physicians surveyed, they have observed patients experiencing withdrawal symptoms from pregabalin, with the most commonly reported symptoms being displeasure and high aggression. Regarding the nationality of pregabalin-misusing patients, 58.3% of the interviewed physicians reported to be rather in contact with foreign patients, mainly from Northwest Africa (Maghreb). Only 45.0% of the surveyed physicians prescribe pregabalin. Among patients who developed behavioral problems while taking pregabalin, none of the physicians (0.0%) showed a tendency to continue pregabalin at the same dose; all respondents chose to reduce/substitute/discontinue. Conclusion Our study has provided confirmatory evidence that the use of pregabalin presents a significant issue in forensic and prison medicine across German-speaking countries. Prescribing pregabalin in this field can compound use disorder problems and exacerbate challenges in daily life for those in forensic institutions or prisons. It is necessary that all physicians who prescribe pregabalin are clearly informed about the management (including the risks) of this drug.